Anchoring ultra-small TiO2 quantum dots onto ultra-thin and large-sized Mxene nanosheets for highly efficient photocatalytic water splitting. Issue 15 (1st August 2021) - Li, Weiming; Zhuang, Chunqiang; Li, Yuanli; Gao, Chunlang; Jiang, Wenshuai; Sun, Zaicheng; Qi, Kezhen
Abstract: The common strategy for the design of photocatalytic materials is to load small-sized cocatalysts onto large-sized photocatalysts for efficient charge separation. In this study, a new design strategy is presented to anchor small-sized TiO2 photocatalysts onto large-sized Ti3 C2 -Mxene cocatalysts, which can provide enriched active sites to receive photo-generated electrons, thus achieving fast charge separation. Based on this strategy, the 4h-hydrogen production rate of the optimized photocatalytic system (62.5 μmol) is 15.2 times higher than that of pure TiO2 (4.1 μmol), strongly demonstrating the feasibility of our design strategy. The strategy here presents an effective way to design novel photocatalytic systems with superior photocatalytic properties.